Peran Media Sosial dalam Pendidikan Politik: Analisis Tayangan Meet Nite Live bagi Mahasiswa Ilmu Politik - Siti Nisaussangadah; Wilda Afriani; Khoerotun Nisa Liswati (Professional: Jurnal Komunikasi dan Administrasi Publik, 2026)
The development of digital technology has significantly transformed the way people access political information, particularly through social media, which has become increasingly dominant among university students. This study aims to analyze the role of the Meet Nite Live program in improving the political understanding of Political Science students in the digital era. The study employs a qualitative approach using the agenda setting theory as an analytical framework to examine how media shapes audience attention and interpretation of political issues. The analysis focuses on five aspects: issue salience, presentation style, intensity of exposure, transfer of salience, and meaning-making effects. Data were collected through interviews, observations, and documentation involving fifth-semester students of the Political Science Program at the Faculty of Social and Political Sciences, Universitas Bangka Belitung. The findings reveal that Meet Nite Live contributes to enhancing students’ political understanding through communicative, contextual, and accessible presentations of political issues. The emphasis on topics such as corruption, geopolitics, and public policy increases students’ attention toward political matters, while repeated exposure through digital platforms strengthens their comprehension. Furthermore, the program encourages critical thinking and raises students’ awareness of socio-political realities. This study demonstrates that social media functions not only as a source of entertainment and information but also as an effective medium for political education in improving the political literacy of young generations in the digital era.